Complete sets of monosubstituted cyclomaltohexaoses (α-cyclodextrins) as precursors for further synthesis - Řezanka, Michal; Jindřich, Jindřich (Carbohydrate research, 2011)
Alkylation of cyclomaltohexaose (α-cyclodextrin, α-CD) with allyl or cinnamyl bromide, followed by peracetylation of remaining hydroxyl groups and separation of isomers, resulted in the set of peracetylated 2(I)-O-, 3(I)-O- and 6(I)-O-alkylated α-CDs in up to 27% yields. Ozonolysis or oxidative cleavage of peracetylated allyl or cinnamyl derivatives resulted in a complete set of peracetylated 2(I)-O-, 3(I)-O- and 6(I)-O-formylmethyl or carboxymethyl derivatives that are useful precursors for preparation of regioselectively monosubstituted derivatives of α-CD. Moreover, a quick method to recognize single 2(I)-O-, 3(I)-O- and 6(I)-O-monosubstituted peracetylated CDs from one another using only their (1)H NMR spectra has been proposed.
Keywords: kyseliny karboxylové; sloučeniny ruthenia; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; alkylace; Aldehydes; alpha-Cyclodextrins; aldehydy; oxidace-redukce; Copper Sulfate; Acetylation; Alkylation; Catalysis; Carboxylic Acids; acetylace; Oxidation-Reduction; Ruthenium Compounds; alfa-cyklodextriny; síran měďnatý; katalýza